1996
DOI: 10.1530/eje.0.1340373
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of transforming growth factor β1 in rat thyroid hyperplasia is thyrotropin induced and time dependent

Abstract: Forty-three 8-week-old male Wistar rats were studied to evaluate temporal changes of transforming growth factor beta1, (TGF-beta1) mRNA levels in thyroid tissue during pharmacologically induced goiter. Four rats were treated with purified bovine thyrotropin (TSH; Ambinon, 2 mU/day sc) for 7 days before being sacrificed. Thirty-one were treated with propylthiouracil (PTU), added to their drinking water at a concentration of 0.2 g%, and subsequently were sacrificed as follows: five after 1 week (PTU-1): five aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
(13 reference statements)
2
17
0
Order By: Relevance
“…In rats injected with either TSH or with drugs that stimulate endogenous TSH secretion, such as methimazole or propylthiouracil (PTU), an increase in TGF-b1 production has been observed (28). In similar studies Logan et al (29) demonstrated an increase in TGF-b1 mRNA during goiter progression, while it decreased with goiter involution as it will be discussed below.…”
Section: Tsh Effectsmentioning
confidence: 94%
“…In rats injected with either TSH or with drugs that stimulate endogenous TSH secretion, such as methimazole or propylthiouracil (PTU), an increase in TGF-b1 production has been observed (28). In similar studies Logan et al (29) demonstrated an increase in TGF-b1 mRNA during goiter progression, while it decreased with goiter involution as it will be discussed below.…”
Section: Tsh Effectsmentioning
confidence: 94%
“…Some forms of epithelial hyperplasia are known to be associated with aberrant TGF 1-mediated growth control (Cui et al 1995, Roberts 1998, but clarification of the role for TGF 1 in MNTG is clouded by conflicting reports; Perlino et al (1996), for example, have reported a reduction in TGF 1 in hyperplastic, compared with normal, thyroid tissue, while a contemporary report (Morosini et al 1996) has recorded higher levels in recurrent goitre after thyroid surgery than in patients remaining in remission. Nevertheless, the evidence from the rat model implicating a critical role of TGF 1 in the limitation of iodide-deficiency goitre suggests that dysregulation of the stimulatory growth factor profile of the hyperplasia of MNTG may include a key change in TGF 1 bioavailability, which is clearly deserving of further study.…”
Section: Latent and Activated Forms Of Tgf And Their Receptorsmentioning
confidence: 99%
“…Thyrocytes from different species produce high amounts of TGF␤ in response to TSH (Contempre et al, 1996;Kolaja and Klaassen, 1998;Morosini et al, 1996;Pekary et al, 1995;Roger, 1996). VEGF, unlike GM-CSF and TGF␤, has been shown to inhibit the development of DC from hematopoietic progenitors (Gabrilovich et al, 1996(Gabrilovich et al, , 1998(Gabrilovich et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%